Genome-wide identification of potential odontogenic genes involved in the dental epithelium-mesenchymal interaction during early odontogenesis - Jiawen Chen; Tianyu Sun; Yan You; Binbin Lin; Buling Wu; Jingyi Wu (BMC Genomics, 2023)
Abstract Background Epithelium-mesenchymal interactions are involved in odontogenic processes. Previous studies have focused on the intracellular signalling regulatory network in tooth development, but the functions of extracellular regulatory molecules have remained unclear. This study aims to explore the gene profile of extracellular proteoglycans and their glycosaminoglycan chains potentially involved in dental epithelium-mesenchymal interactions using high-throughput sequencing to provide new understanding of early odontogenesis. Results Whole transcriptome profiles of the mouse dental epithelium and mesenchyme were investigated by RNA sequencing (RNA-seq). A total of 1,281 and 1,582 differentially expressed genes were identified between the dental epithelium and mesenchyme at E11.5 and E13.5, respectively. Enrichment analysis showed that extracellular regions and ECM-receptor interactions were significantly enriched at both E11.5 and E13.5. Polymerase chain reaction analysis confirmed that the extracellular proteoglycan family exhibited distinct changes during epithelium-mesenchymal interactions. Most proteoglycans showed higher transcript levels in the dental mesenchyme, whereas only a few were upregulated in the epithelium at both stages. In addition, 9 proteoglycans showed dynamic expression changes between these two tissue compartments. Gpc4, Sdc2, Spock2, Dcn and Lum were expressed at higher levels in the dental epithelium at E11.5, whereas their expression was significantly higher in the dental mesenchyme at E13.5, which coincides with the odontogenic potential shift. Moreover, the glycosaminoglycan biosynthetic enzymes Ext1, Hs3st1/5, Hs6st2/3, Ndst3 and Sulf1 also exhibited early upregulation in the epithelium but showed markedly higher expression in the mesenchyme after the odontogenic potential shift. Conclusion This study reveals the dynamic expression profile of extracellular proteoglycans and their biosynthetic enzymes during the dental epithelium–mesenchymal interaction. This study offers new insight into the roles of extracellular proteoglycans and their distinct sulfation underlying early odontogenesis.